SUSTENTABILIDADE DE SISTEMAS DE CULTIVOS IRRIGADOS ORGÂNICO E CONVENCIONAL DE BASE FAMILIAR - Gomes, Maryjane Diniz de Araújo; Nonato Távora Costa, Raimundo; Gamarra Rojas, Guillermo; Rodrigues de Oliveira, Francisco Tiago; Gonçalves Nunes, Kenya (IRRIGA, 2021)
SUSTAINABILITY OF ORGANIC AND CONVENTIONAL IRRIGATED SYSTEMS BASED ON FAMILY FARMING MARYJANE DINIZ DE ARAÚJO GOMES1; RAIMUNDO NONATO TÁVORA COSTA2; GUILLERMO GAMARRA ROJAS3; FRANCISCO TIAGO RODRIGUES DE OLIVEIRA4 E KENYA GONÇALVES NUNES2 1 Instituto Federal de Ciência e Tecnologia do Pará, BR 316, km 65, Campus Castanhal, s/n, CEP. 68740-970, Castanhal, Pará, Brasil, maryjane.gomes@ifpa.edu.br 2 Departamento de Engenharia Agrícola, Universidade Federal do Ceará, Avenida Humberto Monte, s/n, Campus do Pici, Bloco 804, Caixa Postal 12.168, CEP. 60450-760, Fortaleza, Ceará, Brasil, rntcosta@ufc.br, kenyagnunes@gmail.com 3 Departamento de Economia Agrícola, Universidade Federal do Ceará, Avenida Humberto Monte, s/n, Campus do Pici, Bloco 807, Caixa Postal 6017, CEP. 60450-760, Fortaleza, Ceará, Brasil, ggamarra@terra.com.br 4 Agronomic Engineer, Agrocert, Guaraciaba do Norte, Ceará, Brasil, tiago.oliveiraagro@hotmail.com 1 ABSTRACT This study was conducted at two farms: Carcará Farm, certified by Associação de Certificação Instituto Biodinâmico, and at Estufa Limoeiro Farm, of conventional cultivation. They were located in Guaraciaba do Norte, Ceará, at the geographic coordinates 04°10’52” South, 40°49’41” West, and elevation of 885 m. The main objective of this research was to compare, based on economic, social and environmental indicators, two irrigated production systems, one organic one and a conventional. Data were collected through interviews with the farmers. Generation of jobs, added value, and the farmer’s income was analyzed as variables associated with the socioeconomic dimensions. For the environmental analysis, the biological activity of the soil was evaluated using the variables organic carbon (OC), microbial biomass carbon (MBC), soil basal respiration (SBR), microbial quotient (qMIC) and metabolic quotient (qCO2). The organic cultivation system provided a generation of direct jobs per unit area three times higher than the average of irrigated agriculture in the Brazilian semi-arid region, characterizing it as a system of greater social contribution compared to the conventional system, the organic farming system showed a lower risk associated with the economic dimension. The production unit with organic cultivation had higher environmental sustainability since the soil is in more satisfactory physical and chemical conditions for developing microorganisms. Keywords: irrigation, sustainable development, generation of the job, social contribution. GOMES, M. D. A.; COSTA, R. N. T.; ROJAS, G. G.; OLIVEIRA, F. T. O.; NUNES, K. G. SUSTENTABILIDADE DE SISTEMAS DE CULTIVOS IRRIGADOS ORGÂNICO E CONVENCIONAL DE BASE FAMILIAR 2 RESUMO A pesquisa foi realizada na Fazenda Carcará, certificada pela Associação de Certificação Instituto Biodinâmico, e na Fazenda Estufa Limoeiro, de cultivo convencional. As fazendas estão localizadas no município de Guaraciaba do Norte, Ceará, com coordenadas geográficas 04°10’52’ sul, 40°49’41’’ oeste e altitude de 885 m. Teve como objetivo avaliar comparativamente, a partir de indicadores de sustentabilidade econômica, social e ambiental, dois sistemas irrigados de produção, um orgânico e outro convencional. A geração de empregos, o valor agregado e a renda do agricultor, foram analisados como variáveis associadas às dimensões socioeconômicas. Na análise ambiental, foi avaliada a atividade biológica do solo através das variáveis: carbono orgânico (CO), carbono da biomassa microbiana (CBM), respiração basal do solo (RBS), quociente microbiano (qMIC) e metabólico (qCO2). O sistema de cultivo orgânico proporcionou uma geração de empregos diretos por unidade de área três vezes superior à média da agricultura irrigada do semiárido brasileiro, caracterizando-o como um sistema de maior contribuição social. Um menor risco associado à dimensão econômica, comparativamente ao sistema de cultivo convencional. A unidade de produção com cultivo orgânico teve maior sustentabilidade ambiental visto que o solo se encontra em condições físicas e químicas mais satisfatórias para o desenvolvimento de microrganismos. Palavras-chave: irrigação, desenvolvimento sustentável, geração de emprego, contribuição social.